Investments unlimited a novel about DevOps, security, audit compliance, and thriving in the digital age - Beal, Helen; Bensing, Bill; Cox, Jason; Edenzon, Michael; Pal, Tapabrata; Queern, Caleb; Rzeszortarski, John; Vega, Andres; Willis, John (IT Revolution Press, 2024)
Investments Unlimited, Inc. has accomplished what many other firms in their industry have failed to do: they have successfully navigated the transition from legacy ways of working to the digital frontier. With the help of DevOps practices, Investments Unlimited delivers value to its customers with speed and agility. But now, all that work is about to fall apart. Sure, DevOps helped the company adapt, but it also failed them. While features moved through the organization swiftly, their governance process became inundated with friction, frustration, and failure. And now, their inability to deliver what they promise has led regulators to slap them with an MRIA (matter requiring immediate attention), the final warning before cease-and-desist letters and fire sales. With the future of Investments Unlimited on the line, a cross-functional team of executives and engineers has just months to develop a modern governance process that satisfies regulators but doesn't slow down the company's ability to compete in the market. It is up to this ragtag team to navigate trials, tribulations, site failures, and supply chain attacks, all on their path to save the company from disaster. In the vein of the bestselling The Phoenix Project and The Unicorn Project, Investments Unlimited radically rethinks how organizations can handle the audit, compliance, and security of their software systems-even in highly regulated industries. By introducing concepts, tools, and ideas to reimagine governance, Investments Unlimited catalyzes a more humane way to enable high-velocity software delivery that is inherently more secure.